Isolation and characterization of nitrate reductase deficient mutants of the ectomycorrhizal fungus Hebeloma cylindrosporum - Marmeisse, Roland (The New phytologist, 1998)
To clarify the role of the fungal nitrate assimilation pathway in nitrate reduction by mycorrhizal plants, nitrate reductase (NR)-deficient (NR- ) mutants of the ectomycorrhizal basidiomycete Hebeloma cylindrosporum Romagnesi have been selected. These mutants were produced by u.v. mutagenesis on protoplasts originating from homokaryotic mycelia belonging to complementary mating types of this heterothallic tetrapolar species. Chlorate-resistant mutants were first selected in the presence of different nitrogen (N) sources in the culture medium. Among 1495 chlorate resistant mycelia, 30 failed to grow on nitrate and lacked a detectable NR activity. Growth tests on different N sources suggested that the NR activity of all the different mutants is specifically impaired as a result of mutations in either the gene coding for NR apoprotein or genes controlling the synthesis of the molybdenum cofactor. Furthermore, restoration of NR activity in some of the dikaryons obtained after crosses between the different mutant mycelia suggested that not all the selected mutations mapped in the same gene. Utilization of N on a NH4 15 NO3 medium was studied for two mutant strains and their corresponding wild-type homokaryons. None of the mutants could use nitrate whereas 15 N enrichment values indicated that 13-27% of N present in 13-d-old wild-type mycelia originated from nitrate. Apparently, the mutant mycelia do not compensate their inability to use nitrate by a more efficient use of ammonium. These different NR mutants still form mycorrhizas with the habitual host plant, Pinus pinaster (Ait.), making them suitable for study of the contribution of the fungal nitrate assimilation pathway to nitrate assimilation by mycorrhizal plants